2009
DOI: 10.1016/j.jacc.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Transient Local Injury Current in Right Ventricular Electrogram After Implantable Cardioverter-Defibrillator Shock Predicts Heart Failure Progression

Abstract: Objectives This study aimed to identify an early marker of functional impairment after an ICD shock as a predictor of heart failure progression. Background The ICD population has substantial risk of death due to progressive pump failure. Methods Near field (NF) bipolar right ventricular (RV) electrograms (EGMs) during induced ventricular fibrillation (VF) and 10 seconds after rescue ICD shock were analyzed in 310 patients (mean age 59±14.5 years, 219 male [71%]) with structural heart disease, NYHA class I–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…By prolonging the time of detection to longer settings, it is not surprising that fewer inappropriate therapies were delivered; previous studies have shown that most inappropriate therapies are determined by high-rate conducted atrial arrhythmias or lead noises, both of which are influenced favorably by a longer NID. [7][8][9][10][11][12][13][14][15][16] Nevertheless, in terms of the recent hypothesis of a possible association between unnecessary ATPs and increased risk of adverse events in PP, the present data provide a clear indication for a programming strategy that can safely reduce inappropriate therapies in SP patients as well.…”
Section: Inappropriate Therapiesmentioning
confidence: 66%
“…By prolonging the time of detection to longer settings, it is not surprising that fewer inappropriate therapies were delivered; previous studies have shown that most inappropriate therapies are determined by high-rate conducted atrial arrhythmias or lead noises, both of which are influenced favorably by a longer NID. [7][8][9][10][11][12][13][14][15][16] Nevertheless, in terms of the recent hypothesis of a possible association between unnecessary ATPs and increased risk of adverse events in PP, the present data provide a clear indication for a programming strategy that can safely reduce inappropriate therapies in SP patients as well.…”
Section: Inappropriate Therapiesmentioning
confidence: 66%
“…14 Another study showed that a local injury current on near-field bipolar right ventricular electrogram (EGM) after induced ventricular fibrillation (VF) rescue ICD shock is associated with increased risk of congestive heart failure (CHF) progression, future hospitalizations due to CHF exacerbation, and subsequent heart failure death. 15 These results showed that ICD shock was associated with a markedly increased risk of death. Using anti-tachycardia pacing (ATP) as the first therapy for fast ventricular rhythms has been shown to minimize ICD shock and their potentially detrimental effects.…”
Section: Sample Sizementioning
confidence: 94%
“…34 The instantaneous emergence of a transient local injury current on the right ventricular electrogram (EGM) after an induced VF shock, not present during the immediately preceding sinus rhythm, identified patients who were at Ϸ2.5 times increased risk of HF and death following spontaneous VTA shocks. 37 Two related observations raise concern for mortality effects of shocks. First, inappropriate shocks increase mortality risk by 2 to 4 times.…”
Section: Sweeneymentioning
confidence: 99%